Comparative study on the dynamic response of an out-of-plane gradient bionic sandwich circular plate under two types of impact loading - Wang, Hairen; Lei, Jianyin; Chen, Junfei; Li, Yugen; Peng, Jun; Ma, Xiaoli (Frontiers in Materials, 2024)
Out-of-face gradient sandwich structures have been widely studied for their excellent impact resistance. One uniform and two out-of-plane gradient cores are proposed based on the bionic structure of Royal Water Lily, and the midspan deflection of the back panel and the energy absorption of the out-of-plane gradient sandwich structures under various blast loads are studied. Two frequently adopted methods of explosive loading are applied to the sandwich panels, and the responses are contrasted for the loads applied as a time-dependent pressure history versus imposition of the initial velocity. The effect of the fluid–structure interaction is considered in the blast impulsion, and the dynamic responses of the sandwich structures with different out-of-plane density arrangements are analyzed under two loading approaches. Results show that the energy absorption of the core layer under the prescribed velocity approach is approximately 3–5 times that of the applied pressure approach, while the back panel deflections of different out-of-plane gradient sandwiches are similar. There are significant differences in the deformation mechanisms of structures under these two types of impact loads. Under the same type of impact load, the core compression process of the out-of-plane positive gradient sandwich panel is decoupled from the whole tensile bending deformation process of the structure, whereas the core compression process of the out-of-plane negative gradient sandwich panel is strongly coupled with the whole tensile bending deformation process of the structure. The related research will lay the foundation for an in-depth understanding of the theoretical study of the impact of out-of-face gradient sandwich structures.